Contemporary Political and R&D Determinants of the Level of the United States Defence Spending (Economic and Political Thought, 2019)
The aim of the publication was to analyse political and research anddevelopment conditions for the level of defense spending in the USA. Theyare of key importance for shaping the Pentagon military budget in conditionsin which it seems very difficult to grasp the state of threats to which an‘adequate’ level of financing would be an answer.The debate on the level of defense expenditures required to ensurethe security of the state is everlasting. There are two decisive elements fordetermining defense expenditures. First, political circumstances, both ofinternal ones (the Republicans are more inclined to spend more on defensethan the Democrats) and external ones (using military capabilities to keephegemonistic position of the United States, including vis-à-vis allies andadversaries); second, research and development circumstances aimed atensuring technological supremacy of the United States in the world andhaving positive implications for military and civilian sectors.
Keywords: defence expenditures, guns vs. butter, the United States, the Democrats, the Republicans, R&D, DARPA